THE APPLICABILITY ESTIMATES FOR DOPPLER FREQUENCY FILTERING IN CARTESIAN COORDINATES AND COMPARE THE RADAR FILTERING FOR DIFFERENT WAVELENGTHS - S. A. Gorshkov; V. N. Zavizhenets (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The Doppler frequency features in the filtration problem of Cartesian coordinates and total velocity vector of observed objects for radar survey are considered. Comparative analysis of filtration parameters under the radar survey for different wavelengths, are held.